"It was in Control of Me": Notions of Addiction and Online Child Sexual Exploitation Material Offending. (February 2023) - Rimer, Jonah R.; Holt, Karen
This paper focuses on notions of "addiction" among users of online child sexual exploitation material (CSEM) through a comparative analysis of two qualitative studies. The first is a 17-month anthropological ethnography (participant observation, interviews, and focus groups) in UK group programs for CSEM users, and the second is based on interviews with individuals in sexual offense treatment units of a US prison. We thematically analyze the narratives of 103 CSEM users at different timepoints and settings from pre-trial to incarceration. Those citing "addiction" focused on three areas. First was pornography progression. Second were perceived indicators of "addiction" and alignment/analogy to other addictions, including ideas about losing control; ignoring detrimental consequences and continuing; physiological signs similar to withdrawal; likening to substances; and progression from "softer" to "harder" material. Third, less common was rejecting the "addiction" label, citing choice and responsibility. We situate these results within debates and literature regarding pornography and Internet "addiction"; implications of the label; societal conceptions of sexual offending; harms of CSEM; and treatment/prevention considerations. Lastly, highlighting the merit of interdisciplinary comparative qualitative analysis, we demonstrate similarities in narratives despite differences in location, timeframe, setting, conviction status, intervention programming, and research methods.